2007
DOI: 10.1682/jrrd.2006.08.0094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pain and depression on fear of falling, mobility, and balance in older male veterans

Abstract: Abstract-This study determined the extent to which pain and depression influenced changes in fear of falling, mobility, and balance in older veterans with mobility disorders. Data were reviewed from 95 consecutive patients (aged 60 to 95 yr) who attended the Geriatric Gait and Balance Disorders Clinic at the Malcom Randall Department of Veterans Affairs Medical Center between 1998 and 2000. All subjects performed an individualized exercise program and were assessed four times over 12 weeks with a standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
1
15
0
11
Order By: Relevance
“…As características e os locais de dor que aumentaram a ocorrência de queda foram queixa de dor em geral 10,19 , dor no pé 3,11,17 , dor no quadril 20 , dor em dois ou mais locais 21 , dor em região dorsal e cervical 22 , dor em duas ou mais articulações 12 , dor em locais diferentes de membros inferiores 3 , dor generalizada de moderada a intensa 3 , dores mais intensas 12 e dores que interferem nas atividades diárias 4,12 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…As características e os locais de dor que aumentaram a ocorrência de queda foram queixa de dor em geral 10,19 , dor no pé 3,11,17 , dor no quadril 20 , dor em dois ou mais locais 21 , dor em região dorsal e cervical 22 , dor em duas ou mais articulações 12 , dor em locais diferentes de membros inferiores 3 , dor generalizada de moderada a intensa 3 , dores mais intensas 12 e dores que interferem nas atividades diárias 4,12 .…”
Section: Discussionunclassified
“…A Associação Internacional para Estudo da Dor propõe a duração de três meses para caracterizar dor crônica para fins clínicos e seis meses para fins de pesquisa, mas isso nem sempre é seguido e tem sido causa de fragilidade na comparação entre os estudos. A prevalência de dor entre idosos no Brasil e no mundo varia de 37% a 70%, e essa variabilidade depende do critério de dor crôni-ca, da idade e procedência da população, dos locais de dor e dos delineamentos dos estudos, entre outros 8,9,10 .…”
Section: Introductionunclassified
See 2 more Smart Citations
“…15 The presence of depression and painful symptoms in the elderly, quite common among hospitalized patients, are responsible for favoring immobility. 16 Concerning hospitalization time, Huusko et al 17 found that elderly individuals with proximal femoral fractures remained, in average, 34 days in hospital after intensive geriatric treatment (CMIR). Elderly individuals submitted to CR remained in hospital for about 42 days.…”
Section: Discussionmentioning
confidence: 99%